Congenital Heart Disease Long‐term Improvement in Functional hEalth (CHD LIFE): A partnership programme to improve the long‐term functional health of children with congenital heart disease in Queensland. (6th July 2020) - Eagleson, Karen; Campbell, Miranda; McAlinden, Bronagh; Heussler, Helen; Pagel, Susan; Webb, Kerri‐Lyn; Stocker, Christian; Alphonso, Nelson; Justo, Robert
Abstract : Children who undergo open‐heart surgery in the first year of life for congenital heart disease (CHD) are at high‐risk for impaired development across multiple domains. International recommendations include systematic periodic developmental surveillance into adolescence and the establishment of long‐term follow‐up programmes. This article describes the establishment and evolution of the Queensland Paediatric Cardiac Service neurodevelopmental follow‐up programme – CHD LIFE (Long‐term Improvement in Functional hEalth). Contextualising best practice recommendations to ensure a family‐centred and sustainable approach to understand and support the long‐term functional health needs of high‐risk children with CHD as standard care was needed. We describe the transition from a centralised pilot Programme to the implementation of an integrated statewide approach aimed at delivering consistent high‐level standards of care and a platform to evaluate therapeutic interventions.